EFFECTIVENESS OF A BOWEL MANAGEMENT PROGRAM IN TREATING FECAL INCONTINENCE IN POST OPERATIVE PEDIATRIC POPULATION - JAMEEL , M; CHAUDHARY , MA; CHANDNI, .; AYESHA, . (Biological and Clinical Sciences Research Journal, 2024)
Fecal incontinence in pediatric patients post-surgery can significantly impair quality of life. Effective management strategies are critical for these patients, particularly those recovering from surgeries such as Anorectal Malformation (ARM) repair, Hirschsprung’s disease corrections, spine surgeries, or other perineal procedures. Objective: To evaluate the effectiveness of a bowel management program (BMP) in reducing fecal incontinence as measured by the Cleveland Score in postoperative pediatric patients. Methods: This prospective observational study was conducted at the Department of Pediatric Surgery, The Children Hospital, PIMS Islamabad, from July 2023 to April 2024. Seventy pediatric patients who had undergone surgery for ARM, Hirschsprung’s disease, spine surgery, or other perineal surgeries and were experiencing fecal incontinence were enrolled. Patients were selected based on clinical history diagnosed by a consultant pediatric surgeon. The parents of these patients were educated about and enrolled in the BMP. Clinical evaluations using the Cleveland Score were recorded at the program's initiation and one month after its conclusion. Statistical significance was assessed using paired t-tests. Results: Initial mean Cleveland Scores were significantly reduced from 12.99 ± 3.15 at the start of the BMP to 6.56 ± 2.89 one month post-intervention (p < 0.001). 75.7% of the patients achieved a Cleveland Score of less than 5, indicating a substantial reduction in fecal incontinence. Conclusion: The bowel management program proved highly effective in managing fecal incontinence in postoperative pediatric patients, particularly those undergoing ARM surgery. This intervention significantly improved the Cleveland Scores and, consequently, the quality of life in affected children.